Community-Building in Cyberspace - Jankowski, Nicholas W.; Malina, Anna (Javnost-The Public, 1998)
This article explores two of the central theoretical perspectives for promoting and understanding community-building initiatives in cyberspace. One is referred to as “virtual democracy” and contains reference to many of the key concepts taken from classical democratic theory: universal access to information, participation in public debate and political decision-making, empowerment and equality of citizenry. The other perspective, urban entrepreneurialism, is based on an analysis of late capitalism and the place of consumption in determination of self, culture and society. Proponents of this second perspective see possibilities for urban regeneration and economic renewal through emphasis on locally-situated entrepreneurialism operating within a global market. A case study of community-building in cyberspace currently being compiled - the Craigmiller Community Information Service (CCIS) Network in Edinburgh, Scotland - is sketched in the remainder of the article. Although the case clearly reflects aspects of these two perspectives in its stated objectives, limited evidence is found among user groups in the housing estate expressing value for and use of network services. In spite of this, both users and network spokesmen remain optimistic that the initiative will eventually contribute to both entrepreneurial and community-building aspirations shared for the Craigmiller housing estate.